ANALISIS SISTEM PEMBANGKIT LISTRIK HYBRID TENAGA SURYA DAN ENERGI UTILITAS MENGGUNAKAN INVERTER 1500WATT PADA KELISTRIKAN RUMAH TINGGAL - Wardana, Wisnu Adi; -, Hamdani (Power Elektronik : Jurnal Orang Elektro, 2024)
Solar power generation (PLTS) is one of the alternative energy sources currently under development. However, the utilization of solar energy has not been optimal due to the low sunlight intensity in Indonesia, which is approximately only around 5 hours per day. To enhance the use of solar energy, this research focuses on the development of a hybrid bidirectional 1500Watt inverter that integrates solar power generation (PLTS) as an alternative energy source with utility energy. The bidirectional inverter can operate in two ways, serving as both an inverter and a rectifier. This configuration allows solar energy to act as the primary source, with utility energy serving as the secondary source. The study also explores the efficiency and power savings that can be achieved by this hybrid system when applied in households.